KERAGAMAN JENIS TANAMAN PADA SISTEM PENGELOLAAN HUTAN KEMASYARAKATAN - Destia Novasari; Rommy Qurniati; Duryat Duryat (Forestry Study Program University Of Mataram, 2020)
Community Forestry is a government policy that aims to reduce the rate of deforestation by involving local communities through optimal, fair, and sustainable use of forest resources while maintaining the preservation of forest and environmental functions. The diversity of plant species is one indicator of the preservation of forest and environmental functions. This study aims to determine the types of plants and cropping patterns carried out related to the characteristics of group members after obtaining Community Forest Utilization Permits. The study was conducted in December 2018. Data collection was carried out by structured interviews with members of the Sinar Harapan farmer group and direct observation in the field. Data is tabulated and analyzed descriptively. The results showed that the planting pattern used in Sinar Harapan group was a simple agroforestry pattern consisting of 8 types of intolerant plants namely avocado (Persea americana), petai (Parkia speciosa), areca nut (catechu area), durian (Durio zibethinus), jengkol (Archidendrom pauciflorum), bananas (Musaceae), candlenuts (Aleurites moluccanus), mahogany (Swietenia mahagoni) and 7 types of tolerant plants consisting of lemongrass (Cymbopogon citratus), cloves (Syzygium aromaticum), jaling (Archidendron bubalinum), chili (Capsicum frutescens) ), pepper (Piper Nigrum), nutmeg (Myristica fragrans), and coffee (Coffea). The diversity of plant species is influenced by farmer characteristics such as age, type of work, activity in the organization, land area, and the number of working days of farmers.